1999
DOI: 10.1111/j.1540-8167.1999.tb00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sinoatrial Parasympathetic Innervation in Humans

Abstract: Stimulation of parasympathetic nerves that innervate the sinoatrial node shortened atrial refractoriness in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 10 publications
0
30
1
Order By: Relevance
“…Quan et al (16,17) previously identified and characterized the parasympathetic innervation of the two posterior FPs by applying direct nerve stimulation to both FPs. Nerve stimulation of the right pulmonary vein-atrial FP decreased atrial refractoriness and slowed sinus CL, demonstrating selective innervation to the SA node.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quan et al (16,17) previously identified and characterized the parasympathetic innervation of the two posterior FPs by applying direct nerve stimulation to both FPs. Nerve stimulation of the right pulmonary vein-atrial FP decreased atrial refractoriness and slowed sinus CL, demonstrating selective innervation to the SA node.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the current understanding of vagal stimulation shortening atrial refractoriness and increasing susceptibility to AF. Additionally, Quan et al (16,17) evaluated atrial refractoriness during nerve stimulation of the posterior epicardial FPs. It was demonstrated that atrial refractoriness decreased in areas of the atria that were densely innervated by parasympathetic nerves.…”
Section: Discussionmentioning
confidence: 99%
“…21 Numerous studies have observed multiple major and small GPs in the atria of mammalian hearts. 19,[22][23][24] These GPs modulate the interaction and balance between the extrinsic and intrinsic autonomic nervous system and contain efferent cholinergic and adrenergic neurons which influence the atrial myocardium, 25 in terms of action potential duration, AERP, and conduction velocity. In many animal studies, autonomic denervation exhibited short-term efficacy.…”
Section: Changes In the Electrophysiological Characteristics In The Tmentioning
confidence: 99%
“…5 This observation is the rationale for implanting vagal nerve stimulator leads in proximity to the left vagus nerve 6 because stimulation of the right vagal nerve might lead to bradycardia. 7 In our patient, the preoperative HR DB and VR, markers of cardiovagal function, were normal. After a surgical procedure involving a tumor that was intimately associated with the right vagus nerve, he developed sinus tachycardia, loss of baroreflex control of heart rate, and right vocal cord paralysis.…”
mentioning
confidence: 50%